Komparasi Kualitas Guru dan Dukungan Administratif: Studi Perbandingan Sekolah di Desa dan di Kota - Hajrawati Hajrawati; Ishak Bagea; Mujiati Mujiati; Nasir Nasir (Journal of Education and Teaching (JET), 2024)
This study highlights the significant differences between educational conditions in rural and urban areas, particularly in terms of teacher quality and administrative support. The gap between schools in rural and urban areas often affects educational outcomes, which ultimately impacts students' opportunities and quality of life. However, research comparing teacher quality and administrative support in rural and urban schools has been limited. Therefore, this study aims to fill this gap by conducting an in-depth comparative study between rural and urban schools. The research method used is a comparative approach to analyze the differences and similarities between rural-based schools and urban-based schools in terms of teacher quality and administrative support. The results indicate that the comparison of teacher quality in rural and urban schools is influenced by two types of support: managerial support and academic support. Teacher quality and administrative support play an essential role in creating a quality and effective learning environment in both rural-based and urban-based schools.